AgroTech village hub: Conceptual framework for digital innovation to reduce economic disparities and support food security in Sukosari Village - Meri Herlina; Nyokro Mukti Wijaya; Fitria Agustina; Nursela Fitriyani; Bayu Agasta (Universitas Negeri Yogyakarta, 2026)
Sukosari Village faces significant economic disparities, characterized by a high poverty rate of 42.03% of a total of 1,230 families, low coverage of social assistance, and inequality in housing quality. Meanwhile, this village has great agrarian potential with 2,150 hectares of agricultural land and 1,191 farming families that have not been optimized. This study aims to analyze the economic gap and local agricultural potential of Sukosari Village, as well as formulate the concept of AgroTech Village Hub as an innovative conceptual framework solution based on digital technology to reduce inequality and sustainably strengthen food security. The research uses a conceptual-innovative approach supported by secondary data analysis from village monographs and relevant scientific literature reviews. Primary data was obtained through field observation to verify the actual condition of the village, while secondary data was sourced from the Sukosari Village Profile and Monograph in 2024. The results of the analysis show that Sukosari Village has great agrarian potential but has not been optimally utilized due to limited access to technology and information. In response, the concept of the AgroTech Village Hub was formulated, which includes five main components: Smart Farming Center, E-Commerce Production House, Digital Creative Studio & Co-Working Space, Virtual Reality AgroEduTour, and Renewable Energy & Sustainability Unit. This concept offers an integrated technology ecosystem that has the potential to increase agricultural productivity, expand access to the digital economy, and strengthen village food security.